‘A fondness for being sad’: some portuguese sources for Elizabeth Barrett Browning’s Poetics of Melancholy in Sonnets from the Portuguese (1850) - Guimarães, Paula Alexandra (2017)
In seeing melancholy as the antithesis of poetic creativity, the Victorians often broke with the traditional Renaissance and Romantic attitudes of equating melancholy moods with artistic or poetic genius. This article proposes to explore how, initially viewed as an emotional and ‘depressed’ woman poet, Elizabeth Barrett Browning tried to resist and escape the sickening disempowerment or abandonment which had affected poets as Felicia Hemans and Letitia Landon, and engage in a new poetics of melancholy in Sonnets from the Portuguese (1850). It demonstrates how the poet plays this poetics out in most of her later sonnets, where she indeed attempts to prove that good poetry can be written without melancholy, even if she herself does not always succeed in this deliberate rejection of ‘dejection’. The article thus intends to suggest, through a brief comparative analysis, that her apparently contradictory poetics of melancholy very probably derived from a specifically Portuguese poetic tradition, namely the ‘fondness for being sad’ of Luís de Camões’, as well as the sorrowful love of Mariana Alcoforado’s epistles (1669) and of Soror Maria do Céu’s mannerist poems, an influence that is supported in the great similarity of motives and language that can be found in the respective texts.